Beberapa Faktor yang Berhubungan dengan Keaktifan Kader Posyandu di Desa Pengadegan Kabupaten Banyumas - Arina Candra Profita (Universitas Airlangga, 2018)
Background: Posyandu is a maternal and baby clinic to decline the infant mortality rate, infant birth rate, and maternal mortality. The success of activities in Posyandu depends on the cadre's activeness. Data obtained from Banyumas district office in 2013 showed that Puskesmas 1 Wangon hads the lowest percentage of active cadres in Banyumas district, especially posyandu in Pengadegan Village (36 cadres) (60%). Aims: This research aimed at identifying some factors related to the activity of cadres in Posyandu of Pengadegan Village, Banyumas Disctrict. Method: This study used an analytic survey method with total sampling of 60 cadres. The independent variables of this research are knowledge, occupation, motivation and government's support while the activeness of cadres is as a dependent variable. The research instruments were questionnaire and cadre attendance document. Data were analyzed descriptively by using Chi Square. Results: The result shows that knowledge, work, motivation and support of posyandu are related to the activity of cadres in Posyandu of Pengadegan Village, Banyumas Disctrict. Cadres' high activeness is influenced by good knowledge about maternal and baby clinic, high motivation, and unemployement. Conclusion: Knowledge, job, motivation and support from other stakeholders are needed to encourage cadres' participation in the maternal and baby clinic. Coaching and refreshing cadres on an ongoing basis and giving them an award can be alternatives to improve their active participation. Keywords: activeness, cadre, Posyandu